Implementation Probing Prompting Learning Model on Students' Mathematical Concepts Understanding Ability and Self Confidence - Dewi Risalah; Novia Yulianti; Iwit Prihatin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The model of Probing prompts is learning with the way the teacher presents nature questions, lead, and dig so that student requires the ability to understand and develop draft mathematics in finished question. The purpose of this study is to find out how the application of the probing prompting learning model to the ability to understand mathematical concepts in terms of students' self-confidence in the material Algebraic Forms class VII SMP Negeri 1 Sungai Raya. The method used in this study is an experimental method, with the experimental form used being the Quasy Experimental Design experiment, and the research design is a 2 x 3 factorial design. The population of this study was all grade VII students at SMP Negeri 1 Sungai Raya consisting of 5 classes, with samples of class VIIG and VIIH taken using the Cluster Random Sampling technique. Based on the analysis of the variance of two paths with unequal cells, it was concluded that there is a significant difference in the ability to understand mathematical concepts between probing prompting and conventional learning models regarding self-confidence in the material of algebraic forms.